Exploring the multidimensional nature of the psychopathy construct in social media context: Insights from Instagram - Mojtaba Elhami Athar (Computers in Human Behavior Reports)
Despite numerous studies examining the relationship between psychopathy and online behaviors, most have relied on measures that assess psychopathy as a unidimensional construct. However, this contradicts the prevailing view in clinical and research settings that define psychopathy as a multidimensional construct. To address this gap in the literature, the current study examined the relationships between multiple dimensions of the psychopathy construct, as measured by the Youth Psychopathic Traits Inventory – Short Version (YPI-S), and indices of cybercrime, cyber abuse, sadfishing, Instagram addiction, and Instagram activity metrics (daily time spent, frequency of sharing stories/posts, and selfie-sharing), as well as indices of successful online careers in the context of Instagram. A sample of 490 university students (aged 18–46 years; M = 23.92, SD = 7.16; 76.32% female) participated by completing an online version of the measures. Results indicated that each component of the psychopathy construct demonstrated unique associations with online behaviors, suggesting that these components may reflect distinct underlying motivations for engaging in specific online activities. Findings underscore the importance of utilizing multidimensional measures of the psychopathy construct in social media research, rather than relying on unidimensional measures such as those assessing Dark Triad or Tetrad traits. Overlooking this approach may lead to a less comprehensive understanding of the nuanced relationships between psychopathy and online behaviors.